Frontiers of water oxidation: the quest for true catalysts. (26th July 2017) - Li, J.; Güttinger, R.; Moré, R.; Song, F.; Wan, W.; Patzke, G. R.
Abstract : Development of advanced analytical techniques is essential for the identification of water oxidation catalysts together with mechanistic studies. Abstract : Development of efficient and economic water oxidation catalysts (WOCs) remains a crucial bottleneck on the way to artificial photosynthesis applications. Over the past few decades, WOC research has turned into a fascinating interdisciplinary field that ranges from bio-inspired molecular design over nanomaterials and thin films to solid materials tuning. Under the umbrella of WOC optimization, advanced in situ / operando analytical techniques are being developed as increasingly powerful tools to elucidate the controversial discussions about the molecular or nanoscale nature of many WOCs. More and more of these approaches also enable the monitoring of possible key intermediates as an essential prerequisite for proposing catalytic mechanisms. This review is organized in three main parts: first, recent highlights outline frontiers in WOC development, such as the benefits of connecting molecular WOCs with solids along with the introduction of molecular concepts into heterogeneous WOC research. Next, a brief overview of emerging in situ / operando approaches demonstrates new options for monitoring WOC transformations. Finally, selected monitoring studies over the entire WOC dimensionality spectrum illustrate interesting cases of catalytic border crossings as new input for WOC construction.